Gaya Desain pada Elemen Pembentuk Ruang dan Elemen Transisi Interior Gereja Santo Antonius Purbayan Surakarta - Devi Yosin Tjia; Andereas Pandu Setiawan (Intra, 2013)
Santo Antonius Purbayan church is the oldestchurch building in Surakarta. This heritage building of DutchColonial period was built in 1916 and still standing to this day, and did not experience much changes in the architecture and interior aspects. The building is a historical evidence of an event that has the value of architectural and interior. The stylescombination of space forming elements and transition elements in the interior is very variative, that are Art & Craft, ArtNouveau, Art Deco, Nieuwe Bouwen, and also to the European Classical style such as the church building at the first in Europethat are Early Christian style, Romanesque and Gothic. The combination of various styles could not be separated fromaspects of function and meaning of a church and has beenadapted to the local climate and conditions.